2009
DOI: 10.3346/jkms.2009.24.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features of Polypoid Lesions of the Gallbladder and Risk Factors of Gallbladder Cancer

Abstract: It is difficult to differentiate benign and malignancy in polypoid lesions of the gallbladder (PLG) by solely depending on imaging studies. Therefore clinicopathologic features of benign and malignant polyps are compared in an attempt to identify the risk factors of malignant polypoid lesions. The medical records of 291 patients who were confirmed to have PLG through cholecystectomy were reviewed and analyzed for age, sex, symptom, associated gallstone, morphology of PLG, size of PLG, number of PLG, and preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
4
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 15 publications
4
100
4
8
Order By: Relevance
“…Several reports showed that polypoid lesion is highly likely to be cancerous if it is sessile and/or solitary, its diameter is equal to or greater than 10 mm, patient's age is equal to or greater than 60 years old, and/or it grows rapidly [28][29][30][31][32]. According to these results, when polypoid lesion of the gallbladder is sessile, has a diameter equal to or greater than 10 mm and/or grows rapidly, it is highly likely to be cancerous and should be resected by cholecystectomy [28][29][30][31][32][33][34][35][36].…”
Section: Cq2: Is a Cholecystectomy Necessary For Polypoid Lesions Of mentioning
confidence: 99%
“…Several reports showed that polypoid lesion is highly likely to be cancerous if it is sessile and/or solitary, its diameter is equal to or greater than 10 mm, patient's age is equal to or greater than 60 years old, and/or it grows rapidly [28][29][30][31][32]. According to these results, when polypoid lesion of the gallbladder is sessile, has a diameter equal to or greater than 10 mm and/or grows rapidly, it is highly likely to be cancerous and should be resected by cholecystectomy [28][29][30][31][32][33][34][35][36].…”
Section: Cq2: Is a Cholecystectomy Necessary For Polypoid Lesions Of mentioning
confidence: 99%
“…For such reason, polypoid lesions of the gallbladder are often detected incidentally. [3,9] However, there are some patients with gallbladder polyps which may suffer nausea, vomiting, and occasional pain in the right hypochondrium, due to intermittent obstructions caused by small fragments of cholesterol that become detached from the gallbladder mucosa. There are descriptions of polyps that protrude greatly obstructing the cystic canal or the primary biliary ducts, causing acute cholecystitis or obstructive jaundice, but these are very rare complications.…”
Section: Symptomatologymentioning
confidence: 99%
“…[1,3,8,34,35] Polyp size has long been noted to be an important factor. Gallbladder polyps larger than 1.5 cm, especially in solitary sessile hypoechogenic polyps, are associated with a risk of malignancy.…”
Section: Prediction Of Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a minority of patients report abdominal symptoms that are similar to those induced by small gallstones that are rarely detached from the mucosa. 6 When cholecystectomy is recommended, many patients wondered about the relief of their symptoms and about any occurrence of new symptoms after removing the gallbladder. However, many studies have reported that the changes in abdominal symptoms after laparoscopic cholecystectomy (LC) may differ according to the selection of patients and their preoperative conditions.…”
Section: Introductionmentioning
confidence: 99%